A closer view of the entrance of the Shiva Temple (Temple 1) - Temples of India Project Team (Jio Institute, 2024)
A closer view of the entrance of the Shiva Temple (Temple 1) in Cluster 1. The antarala (vestibule) of the temple is shallow and devoid of a niche or sculptures. The entrance gate of the garbhagriha (sanctum sanctorum) also shows minimal decoration. The lalatabimba (lintel) has no figure present.